2019
DOI: 10.3390/cancers11020264
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Mechanism of Action Involved in Enhanced Suicide Gene Colon Cancer Cell Killer Effect Mediated by Gef and Apoptin

Abstract: Despite the great advances in cancer treatment, colorectal cancer has emerged as the second highest cause of death from cancer worldwide. For this type of tumor, the use of suicide gene therapy could represent a novel therapy. We recently demonstrated that co-expression of gef and apoptin dramatically inhibits proliferation of the DLD-1 colon cell line. In the present manuscript, we try to establish the mechanism underlying the enhanced induction of apoptosis by triggering both gef and apoptin expression in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…Notably, caspase 3 is activated during the overexpression of E4orf4 in cancer cells but doesn't seem to be vital for the induction of cell death [97]. Other caspases 9 and 7 are also significant for CAV-Apoptin and NS1 induced cell death [92][93][94]102].…”
Section: Importance Of Caspasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, caspase 3 is activated during the overexpression of E4orf4 in cancer cells but doesn't seem to be vital for the induction of cell death [97]. Other caspases 9 and 7 are also significant for CAV-Apoptin and NS1 induced cell death [92][93][94]102].…”
Section: Importance Of Caspasesmentioning
confidence: 99%
“…The initiation of mitochondrial cell death by means of mitochondrial outer membrane permeabilization (MOMP) is a universal effect of these viral proteins. The pro-apoptotic proteins targeting the mitochondria Bax and Bak are important in Apoptin cancer toxicity as treatment with Apoptin increased the expression of Bax and cells devoid of both are strongly protected against cell death [92,102]. Moreover, studies have presented that Apoptin treatment leads to a loss of mitochondria membrane potential and subsequent release of cytochrome c [92,102,103].…”
Section: Mitochondrial Cell Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…The Food and Drug Administration (FDA) has approvedpreclinical treatments using cetuximab for the treatment of neckand head carcinoma and colorectal carcinoma with EGFR-expressingcancer tumors. This C225 might be a suitable objective for thestructure of nanocarriers to improve the outcome of ATC therapy.Remarkably, some researchers have revealed that for a wide spectrumof cancers, the blend of C225 with CPT-11 equivalents such asPer uorohexane/Gold Nanoparticles (Au-PFH-NPs) has signi cantsynergetic antitumor effects [22][23][24][25], thus, enhancing ATCdiagnostics. However, owing to the reduced vascular dispersal ofC225 and the hydrophobicity of the Au-PFH-NPs, the nanoparticles'(NPs) penetrability in the growth and their quantity in the tumorarea were inherently imperfect, which greatly debilitated theiranticancer e cacy.…”
Section: Introductionmentioning
confidence: 99%
“…It has become evident that further efforts in colorectal cancer research are required, from providing a better understanding of the cellular and molecular mechanisms leading to colorectal neoplasm initiation and progression from adenoma to metastasis, to generating reliable non-invasive detection tests for identifying lesions at early stages, as well as refining the current therapeutic and personalized approaches and developing new ones. The aim of this Special Issue is to cover all aspects of colorectal cancer research, including basic, preclinical, and clinical approaches.The original articles of this Special Issue present innovative findings toward the design of new strategies that may contribute to the fight against colorectal cancer cells, such as treatments that enhance apoptosis-related mechanisms [1,2], chemosensitivity [3-6] and/or radiotherapy [7], and the characterization of new pathways that lead to the identification of specific biomarkers and/or decipher unique mechanisms underlying colorectal cancer initiation and progression. These mechanisms include the transcriptional regulation of DNA repair proteins [8]; the epigenetic regulation of the zinc finger E-box-binding homeobox 1 [9] and the expression of the (pro)renin receptor [10], , and calcium and calcium-activated potassium channels [12]; the contribution of immune cells in the tumor microenvironment [13]; and the identification of genetic aberrations that occur during the transition from adenoma to carcinoma [14].…”
mentioning
confidence: 99%